Managing gender and youth education for sustainable development in Nigeria (2008)
"This study investigated parents, teachers, and undergraduate students' perception of the relationship between a well-managed gender and youth education and sustainable national development. The study was an ex-post facto research. Stratified sampling was used to select the subjects as follows: 100 parents (50 from each sex), 200 hundred teachers (100 males and 100 females) and 300 final year undergraduates (150 from each gender) making 600 subjects. A 44-item questionnaire was developed and validated by the researchers at 0.71 KR-20 reliability coefficient and construct validity coefficient of 0.68 cronbach Alpha. The data were analysed using Pearson's Product Moment statistics. The results of 0.77(parents), 0.88(teachers) and 0.87(students) at 0.01 level of significance, for the youth education was higher than that of the girl-child education of 0.64(parents), 0.81 (students) and 0.85(teachers). Findings showed that religion had been a major barrier to the girl-child education in certain parts of the country. Also the differences between the teachers' and the students' perception of the relationship existing between the girl-child education and sustainable national development can be attributed to the differences in the levels of education and experience. Although the results showed that all respondents agreed that""youth education contributes immensely to sustainable national development but most of them equated youth education to boy-child education and are yet to accord the girl child education the same level of importance. It was thus recommended that governments must be in the vanguard of education provision for all while girlchild education must be accorded the requisite priority. Governments and other stakeholders should be vigorously involved in the provision of quality and holistic education for all irrespective of sex and religion. Those charged with the responsibility of managing the education sector should be given managerial training from time to time, to equip them with modern techniques for optimal performance."